Mainstreaming of the gender perspective in water management:: lessons learned from Chiapas, Mexico - Ruiz Meza, Laura Elena (Sustainability in Debate, 2017)
In the paper I present the findings and learning derived from my research and my experience of incidence to incorporate the gender approach in water management, in Chiapas, south of Mexico. First, I present the linkages between gender and water management and the theoretical references that guided my research. Subsequently, the characteristics of sectoral and androcentric management of water are analyzed, and the position of inequity that rural women live to gain access to control of their rights to water. Findings and obstacles are presented as lessons learned. It concludes with a brief reflection on the challenges and alternatives for change that exist based on the struggles of women’s movements.